Invariant-feature segmentation unlocks robust large-area mapping of mariculture - Ziyu Jiang; Jinyan Xie; Jihao Peng; Huaqing Wu; Yue Liu; Cong Zeng; Yueming Liu; Xiaomei Yang; Ling Cao (Marine Environmental Research, 2026)

High magnetic field-driven assembly of collagen peptide-cerium chelates from fish skin: Microstructure, colloidal stability and absorption behavior - Peihan Wu; Hui Wang; Yueming Hu; Pingwei Wen; Liang Zhang; Peng Zhang; Xiaomei Sha; Zongcai Tu (Food Hydrocolloids, 2026)

Reactive heavy metals govern soil microbial communities: Depth-resolved evidence and disentangled metal-specific effects - Lixue Qiu; Chenle Wang; Fuxing Wu; Yueming Han; Lixun Zhang (Journal of Hazardous Materials, 2026)

Accelerated charge transfer dynamics via a CoFe bimetallic oxide hole transport medium for enhanced photoelectrochemical water oxidation - Jiaxin Mao; Xingyu Zeng; Yuming Wu; Ziyan You; Wenfang Deng; Ming Ma; Yueming Tan (Chemical Engineering Journal, 2026)

Torque teno virus in the lower respiratory tract: association with immunosuppression but not mortality in severe pneumonia—a multicenter retrospective cohort study - Xian Zhang; Lifei Chen; Fang Wang; Xiaofang Xu; Yueming Wu; JunLong Xu; Yongan Xu; Xuwei He (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

High-throughput characterization of local structural imperfections in freestanding oxide membranes by lock-in thermography - Ao Wang; Jinfeng Zhang; Jinxiang Yan; Fang Xu; Qing Wang; Yueming Huang; Minghui Fan; Qiming Lv; Zhengguo Liang; Kunjie Dai; Dazhi Hou; Wenbin Wu; et al. (Science Bulletin, 2026)

Sealing behavior of bolted flange system with double metallic C-rings during prolonged high-temperature operation - Yijun Chai; Yunzhou Wu; Wenhao Yu; Qin Ma; Xiongwei Yang; Yueming Li (Annals of Nuclear Energy, 2026)

Organic matter supply triggers rapid microbial-driven changes in carbon-nitrogen cycling in subterranean estuary sediments - Danqing Sun; Longyun Lai; Yueming Wu; Ying Wu; Jian Li; J. Severino P. Ibánhez; Shan Jiang (Marine Chemistry, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Distinct mowing effects on organic carbon storage and dynamics in Spartina alterniflora and Phragmites australis sediments - Yueming Wu; Danqing Sun; Shan Jiang; Beiyun Xu; Jing Liu; Jian Li; Yiyun Wang; Ying Wu (Ocean & Coastal Management, 2026)

Pharmacological inhibition of USP7 attenuates deltamethrin-induced neuronal ferroptosis via GPX4 stabilization - Minjia Wu; Yang Chen; Peixuan Ma; Wen Pan; Yaqin Deng; Lexing Wei; Guodong Lu; Michael Aschner; Yueming Jiang; Jing Zhou; Xiaowei Huang (Toxicology and Applied Pharmacology, 2026)

Mitigating methane emissions from municipal solid waste in Chinese cities - Yueming Gao; Yang Duan; Wei Zhang; Nana Zhao; Yuan Wang; Zhenyu Ding; Wenjun Wu; Dong Cao; Hongqiang Jiang (Journal of Environmental Management, 2026)

High magnetic field-assisted preparation of food-derived collagen peptide-cerium (III) chelate: reducing oxidative stress and helping restore osteoblast function - Peihan Wu; Zongcai Tu; Hui Wang; Yueming Hu (Food Bioscience, 2025)

Enhancing the output of cellulose-based triboelectric nanogenerators via dual interfacial polarization effects - Feijie Wang; Suyang Wang; Hao Wang; Yichi Liu; Shiqiang Ouyang; Shenzhuo Zhang; Yueming Hu; Junhua Zhao; Shufeng Ma; Zhen Wu; Liqiang Wang (Carbohydrate Polymers, 2025)

Chelation of cerium (III) with fish skin collagen peptides: Improving the in vitro stability and bioavailability of inorganic cerium - Peihan Wu; Zongcai Tu; Hui Wang; Yueming Hu; Jie Cheng; Hai-bin Liu; Pingwei Wen (Food Research International, 2025)

A new point mutation (E198T) in β2-tubulin confers resistance to carbendazim in Fusarium incarnatum - Zelong Peng; Zhili Yuan; Yueming Jin; Furong Chen; Zhiwen Wu; Yiping Hou (Pesticide Biochemistry and Physiology, 2025)

MEK1 inhibition ameliorates mitochondrial-dependent apoptosis induced by deltamethrin in mouse hippocampal neuron HT22 cells - Lexing Wei; Yang Chen; Minjia Wu; Peixuan Ma; Huan Wang; Yueming Jiang; Michael Aschner; Jing Zhou; Guodong Lu; Lina Zhao; Xiaowei Huang (Toxicology in Vitro, 2025)

Remaining useful life prediction of lead-acid battery using multi-phase wiener process-based degradation model - Jun Yang; Yueming Hong; Wenlin Wang; Guohua Wu (Process Safety and Environmental Protection, 2025)

Effects of storage durations on flavour and bacterial communities in Liupao tea - Yueming Liang; Zhusheng Liu; Yuelan Pang; Min Li; Shengmeng Zheng; Fujing Pan; Chunyu Guo; Qianhua Wu; Ting Chen; Qiang Li; Zhonghua Liu (Food Chemistry, 2025)

Freezing or searing: Unraveling the impact of extreme temperatures on poverty in China - Huiming Zhang; Shuyuan Wang; Kai Wu; Yueming (Lucy) Qiu; Shouyang Wang; Yongfan Zhao (Environmental Impact Assessment Review, 2025)

Higher dynamic and turnover yet enhanced organic carbon burial in Spartina alterniflora sediments: A case study in a temperate coastal wetland - Yueming Wu; Beiyun Xu; Danqing Sun; Shan Jiang; Jian Li; Yiyun Wang; Ying Wu (CATENA, 2025)

Modulating allergenicity of prawn tropomyosin (penaeus chinensis) via pulsed electric field-induced conformational changes - Xiangfei Hu; Hui Wang; Yueming Hu; Pingwei Wen; Xiongchen Wu; Zongcai Tu (Food Chemistry, 2025)

An update of aurones: food resource, health benefit, biosynthesis and application - Jiali Yang; Zhengjiao Gao; Zhiqian Yu; Yu Hou; Dingtao Tang; Huiling Yan; Fuwang Wu; Sui Kiat Chang; Yonggui Pan; Yueming Jiang; Zhengke Zhang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2024)

Fermentation by Penicillium polonicum improves the functional components and biological effects of orange peel via producing β-glucosidase without the risk of potential mycotoxins - Yan Liang; Chunling Lai; Liangliang Gao; Qingna Wu; Meiling Huang; Yueming Jiang; Jun Zhang (Food Bioscience, 2024)

Multi-rater Prism: Learning self-calibrated medical image segmentation from multiple raters - Junde Wu; Huihui Fang; Jiayuan Zhu; Yu Zhang; Xiang Li; Yuanpei Liu; Huiying Liu; Yueming Jin; Weimin Huang; Qi Liu; Cen Chen; Yanfei Liu; et al. (Science Bulletin, 2024)

Unravelling the morphology effect of Pt/In2O3 catalysts for highly efficient hydrogen production by methanol steam reforming - Lini Liao; Yong Men; Yueming Wang; Shuyi Xu; Shuya Wu; Jinguo Wang; Zhenrong Yan; Xuelong Miao (Fuel, 2024)

Free and Forced Vibration Characteristics of a Composite Stiffened Plate Based on Energy Method - Xin Gu; Xianzhong Wang; Weiguo Wu; Jie Sun; Yongshui Lin; Yueming Fang (Journal of Marine Science and Engineering, 2024)
The composite stiffened plate has garnered significant attention in the lightweight design of ship structures due to its superior mechanical properties. Although it reduces the structural weight, it also increases vibration sensitivity. Thus, investigating the vibration characteristics of the composite stiffened plate is crucial. This paper proposed a theoretical model based on the energy principle and the improved Fourier series method (IFSM) to analyze the composite stiffened plate vibration characteristics. The model demonstrates high reliability and accuracy, as confirmed through convergence analysis and comparison with experimental results from the published literature. Results indicate that geometry and material parameters significantly impact the natural frequency and can mitigate vibration responses by increasing thickness and stiffness. Additionally, ply design parameters markedly influence the vibration of composite stiffened plates, enhancing low-frequency vibration performance through optimal ply design. The structural parameters of the stiffeners, particularly the height and number of stiffeners, play a crucial role, enhancing stiffness and reducing the vibration responses of the composite stiffened plates.

Identification of groundwater pollution sources and health risk assessment in the Fengshui mining area of Central Shandong, China - Hongyu Li; Jiaxin Wu; Yueming Qi; Chengzhi Su; Dan Jiang; Pei Zhou (Environmental Science and Pollution Research, 2024)

Fe mediated alleviation effect of cadmium toxicity in mangrove Avicennia marina (Forssk.) Vierh - Jian Li; Yueming Wu; Xiaotong Guo; Shan Jiang; Zhanrui Leng; Jiaojiao Xia; Chongyu Zhuo; Hui Jia; Daolin Du (Frontiers in Marine Science, 2023)
Iron (Fe) supply is one of the key factors in alleviating cadmium (Cd) stress in different plants, including mangroves. However, the effects and mechanisms of Fe in mediating the mangrove response to Cd stress still need to elaborate on the level of plant physiology and metabolism. Herein a 40-day hydroponic study was conducted to evaluate the mediating effect of Fe on Cd tolerance of Avicennia marina (Forssk.) Vierh. Results showed that the Fe supply directly improved the activity of ferric chelate reductase (FCR), increased Fe concentration in tissues, enhanced its competitiveness with Cd, and improved Fe bioavailability, thereby reducing the uptake of Cd by plants. Simultaneously, moderate Fe enhanced the photosynthesis and increased concentrations of total phenolics and tannins in both roots and leaves that play a critical role in chelating and immobilizing Cd, thus restricting the Cd translocation from roots to aboveground tissues. Additionally, the application of Fe significantly upregulated the activity of antioxidant enzymes, including POD and PPO and hence scavenging the reactive oxygen species caused by Cd stress. In conclusion, moderate Fe application improved the growth of A. marina and enhanced its tolerance to Cd at physiological and metabolic levels. Therefore, improving Fe bioavailability will reduce the mangrove degradation caused by Cd contamination, and also this may be a potential way to restore contaminated mangrove ecosystems. Protecting and restoring mangroves is not only essential for preserving biodiversity and supporting coastal ecosystems but also crucial for maintaining their role as crucial carbon sinks (i.e., mangrove blue carbon) combating global warming and climate change.

Hexaconazole and binary mixtures of it plus fludioxonil efficiently control tomato leaf mold caused by Cladosporium fulvum - Shuai Hu; Xiuhuan Li; Lele Chen; Yueming Wu; Lingtao Meng; Kai Wang; Beixing Li; Feng Liu (Crop Protection, 2023)

Effects of different high-temperature conduction modes on the ovalbumin-glucose model: AGEs production and regulation of glycated ovalbumin on gut microbiota - Haiqi Chen; Yanru Zhou; Siqiong Zhang; Zuohua Xie; Pingwei Wen; Hui Wang; Yueming Hu; Peihan Wu; Jiaojiao Liu; Qiannan Jiang; Zongcai Tu (Food Research International, 2023)

Microbiota of a seepage face at the mouth of a subterranean estuary: diversity, distribution and substrate dependence - Yueming Wu; Yongjun Wei; Juan Severino Pino Ibánhez; Danqing Sun; Kaiqi Lu; Qianqian Wang; Jian Li; Shan Jiang (Acta Oceanologica Sinica, 2023)

Flavor substances of low-valued red swamp crayfish (Procambarus clarkii) hydrolysates derived from double enzymatic systems - Chujun Li; Zongcai Tu; Wenyu Liu; Chunlin Wu; Yueming Hu; Hui Wang (Food Research International, 2023)

Involvement of miRNAs-mediated senescence and salicylic acid defense in postharvest litchi downy blight - Chunxiao Yin; Lihong Xie; Yanfei Wu; Hongxia Qu; Bao Yang; Liang Gong; Yueming Jiang; Taotao Li (Food Chemistry, 2023)

Multiple metabolomics comparatively investigated the pulp breakdown of four dragon fruit cultivars during postharvest storage - Qixian Wu; Huijun Gao; Ziming You; Zhengke Zhang; Hong Zhu; Mingyang He; Junxian He; Xuewu Duan; Yueming Jiang; Ze Yun (Food Research International, 2023)

Study on structure-activity relationship (SAR) of simplified mirogabalin derivatives as voltage-gated calcium channel α2δ ligands for the treatment of chronic neuropathic pain - Yuanwen Zhang; Yueming Zheng; Qingqing Wu; Fuyun Tian; Chuanjun Ma; Haiyan Xu; Li Zhan; Zhaobing Gao; Guilong Zhao; Huihui Ti (Medicinal Chemistry Research, 2023)

Construction of a Diagnostic Model for Distinguishing Benign or Malignant Bone Cancer by Mining miRNA Expression Data - Yueming Zhang; Jianwei Hu; Tao Li; Shizhu Hao; Xiaotang Wu (Biochemical Genetics, 2023)

MiR-139-5p/ENAH Affects Progression of Hepatocellular Carcinoma Cells - Yueming Zhang; Meng Li; Yinghuan Qiu; Yuhua Wu; Shan Chen; Bin Ni; Ding Tang; Zhouzi Deng; Zhiqiang Hu (Biochemical Genetics, 2022)

RETRACTED ARTICLE: RINT1 is a new suppression target to reduce colon cancer cell growth, migration and invasion through regulating ZW10/NAG-1 expression - Jinheng Xu; Meng Zhao; Shunxian Huang; Qian Wu; Minghe Bai; Xueli Zhao; Jixian Wang; Yueming Hu; Junwei Feng; Zhiyong Zhang (Molecular and Cellular Biochemistry, 2022)

Consequences of Coastal Wetlands Reclamation and the Need for Integrating Impact Assessment of Invasive Alien Plants Species and Coastal Armoring in Life Cycle Assessment (LCA) - Taitiya Kenneth Yuguda; Zhanrui Leng; Yueming Wu; Hui Jia; Sai Zhang; Zhicong Dai; Jian Li; Daolin Du (International Journal of Environmental Research, 2022)

The Impact of Multiple Pond Conditions on the Performance of Dike-Pond Extraction - Jinhao Zhou; Wu Zhou; Qiqi Zhou; Yuanhui Zhu; Fei Xie; Shen Liang; Yueming Hu (Fishes, 2022)
Dike-ponds in fisheries often present multiple pond conditions such as pure, suspended sediment, water bloom, semidry conditions, etc. However, the impact of these conditions on the performance of extracting dike-pond from remote sensing images has not been studied. To solve this problem, we explore the existence of such impacts by comparing the performance of four rule-based methods in two groups of test regions. The first group has few multiple pond conditions, while the second has more. The results show that various measure values deteriorate as the proportion of multiple pond conditions in the regions increases. All four methods performed worse in the second group than the first, where the overall accuracy decreased by 8.80%, misclassification error increased by 3.69%, omission error raised by 10.53%, and correct quantity rate dropped by 8.23%, respectively. The extraction method that ingested multiple pond conditions performed indistinguishably from the other methods in the first group. However, it outperformed the other methods in the second group, with a 4.22% improvement in overall accuracy, a 10.25% decrease in misclassification error, and a 19.03% increase in the correct quantity rate. These findings suggest that multiple pond conditions can negatively impact the extraction performance and should be considered in dike-pond applications that require a precise pond size, number, and shape.

Spatiotemporal dynamics and influencing factors of the global material footprint - Heming Wang; Yao Wei; Yueming Wu; Xinzhe Wang; Yao Wang; Guoqiang Wang; Qiang Yue (Environmental Science and Pollution Research, 2022)

Proteomic and transcriptomic analysis to unravel the influence of high temperature on banana fruit during postharvest storage - Taotao Li; Qixian Wu; Xuewu Duan; Ze Yun; Yueming Jiang (Functional & Integrative Genomics, 2019)

Long-term exposure to low level of fluoride induces apoptosis via p53 pathway in lymphocytes of aluminum smelter workers - Pingjing Wen; Xiaomin Wei; Guiqiang Liang; Yanfei Wang; Yiping Yang; Lilin Qin; Weiyi Pang; Guangqiu Qin; Hai Li; Yueming Jiang; Qijun Wu (Environmental Science and Pollution Research, 2019)

Diagnosing Climate Change and Hydrological Responses in the Past Decades for a Minimally-disturbed Headwater Basin in South China - Yiping Wu; Dongsheng Cheng; Wende Yan; Shuguang Liu; Wenhua Xiang; Ji Chen; Yueming Hu; Qian Wu (Water Resources Management, 2014)

Research on the relationship between the fractional coverage of the submerged plant Vallisneria spiralis and observed spectral parameters - Qian Cheng; Kunqi Wu; Yan Bai; Yueming Hu (Environmental Monitoring and Assessment, 2013)

Comparative analysis of basidiomycetous laccase genes in forest soils reveals differences at the cDNA and DNA levels - Xiangbi Chen; Yirong Su; Xunyang He; Yueming Liang; Jinshui Wu (Plant and Soil, 2013)

Removal of heavy metal ions from wastewater by a novel HEA/AMPS copolymer hydrogel: preparation, characterization, and mechanism - Zhengkui Li; Yueming Wang; Ningmei Wu; Qichun Chen; Kai Wu (Environmental Science and Pollution Research, 2013)